2018
DOI: 10.3390/ijms20010117
|View full text |Cite
|
Sign up to set email alerts
|

Beyond a Measure of Liver Function—Bilirubin Acts as a Potential Cardiovascular Protector in Chronic Kidney Disease Patients

Abstract: Bilirubin is a well-known neurotoxin in newborn infants; however, current evidence has shown that a higher serum bilirubin concentration in physiological ranges is associated with a lower risk for the development and progression of both chronic kidney disease (CKD) and cardiovascular disease (CVD) in adults. The protective mechanisms of bilirubin in CVD, CKD, and associated mortality may be ascribed to its antioxidant and anti-inflammatory properties. Bilirubin further improves insulin sensitivity, reduces low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 144 publications
(172 reference statements)
3
26
0
Order By: Relevance
“…The potential mechanisms behind the protective role of serum bilirubin are as follows: First, serum bilirubin is seen as a potent, endogenous antioxidant reagent because of persistent recovery in intracellular bilirubin redox metabolism. Second, it has been previously demonstrated that STB has a positive association with anti-inflammatory effects, which are a protective factor of CKD ( 37 ). Zucker et al supported the finding that bilirubin could prevent an inflammatory reaction in a mice model of inflammatory colitis by preventing vascular cell adhesion molecule 1 (VCAM-1) -mediated leukocyte infiltration in target tissues ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms behind the protective role of serum bilirubin are as follows: First, serum bilirubin is seen as a potent, endogenous antioxidant reagent because of persistent recovery in intracellular bilirubin redox metabolism. Second, it has been previously demonstrated that STB has a positive association with anti-inflammatory effects, which are a protective factor of CKD ( 37 ). Zucker et al supported the finding that bilirubin could prevent an inflammatory reaction in a mice model of inflammatory colitis by preventing vascular cell adhesion molecule 1 (VCAM-1) -mediated leukocyte infiltration in target tissues ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased HO-1 enzymatic activity is not only essential for MSC maturation, but is also cytoprotective against oxidative stress [58,59]. The antioxidant effects of HO-1 arise from its ability to increase reduced glutathione levels and degrade heme, as well as its ability to increase biliverdin and bilirubin, which have potent antioxidant properties [60,61]. In IR-AKI models, the increased production of HO-1 after MSC administration correlated with decreased levels of 8-hydroxy-2-deoxyguanosine (8-OHdG) and ROS [62].…”
Section: Oxidative Stress In Ir-akimentioning
confidence: 99%
“…As mentioned above, accumulating evidence has shown that bilirubin exerts a protective role against renal disease progression, through various mechanisms 10,11 . Bilirubin also has an immunomodulatory effect, which is expected to reduce graft rejection after kidney transplantation 14,15 . However, scarce data exist regarding the association between serum bilirubin levels and kidney transplant outcomes 19 .…”
Section: Discussionmentioning
confidence: 99%
“…These bene cial effects have largely been attributed to the antioxidant property of bilirubin 12,13 . Recent studies have further suggested that bilirubin may exert anti-in ammatory, immunomodulatory, and endothelial protective effects 14 .…”
Section: Introductionmentioning
confidence: 99%